1997
DOI: 10.1002/(sici)1099-1379(199705)18:3<205::aid-job792>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

The nature and structure of workers' trust in management

Abstract: SummaryThis paper presents a theoretical and empirical analysis of the nature of trust at work. Use is made of the facet approach to generate a de®nitional framework of trust, and this is proposed as a theoretical basis for the analysis of the structural characteristics of trust. Hypotheses regarding the relations between the de®nitional framework and empirical observations were tested by applying Smallest Space Analysis to analyse data collected from a sample of 398 colliery workmen, using questionnaires deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
124
0
5

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(136 citation statements)
references
References 34 publications
7
124
0
5
Order By: Relevance
“…However, additional information again did significantly affect the perception rating. These findings also supported the claim that perception of integrity is also cognitive in nature [28,55]. However, there existed some subtle differences in the impact of additional information between perceptions of ability and of integrity.…”
Section: Discussion For Hypothesissupporting
confidence: 92%
See 1 more Smart Citation
“…However, additional information again did significantly affect the perception rating. These findings also supported the claim that perception of integrity is also cognitive in nature [28,55]. However, there existed some subtle differences in the impact of additional information between perceptions of ability and of integrity.…”
Section: Discussion For Hypothesissupporting
confidence: 92%
“…We therefore concluded that additional information did play a vital role for a person to reach a perception judgment. In fact the above results conformed to the claim that perception of ability is cognitive [28,55], which means that the perception is formed based on trustworthy or untrustworthy acts, rather than one's affective state.…”
Section: Discussion For Hypothesismentioning
confidence: 99%
“…A positive working relationship with one another irrespective of the grade level and designation provide platforms to persevere and create an environment that motivates innovative activities and entrepreneurial dispositions within an organization (Armstrong and Taylor 2014). Some of the things that can foster employee relationships in the world of work includes but not limited to getting to know each other, playing together during break and close of business among others (Clark 2008).…”
Section: Employee Relationshipssupporting
confidence: 80%
“…More recent empirical support comes from a study of coal mineworkers' trust in their managers. Clark and Payne (1997) show that workers' characteristically certain negative assertions about the behavior of managers and about how they, as workers, intend to behave in their interactions with management (trust-relevant statements) are clearly separable from characteristically certain positive assertions about management's behavior and about workers' behavioral intentions (distrust-relevant statements).…”
Section: Trust and Distrust Are Separablementioning
confidence: 99%